Differential effects of film on preschool children's behaviour dependent on editing pace. (26th February 2017) - Kostyrka‐Allchorne, Katarzyna; Cooper, Nicholas R.; Gossmann, Anna Maria; Barber, Katy J.; Simpson, Andrew
Abstract: Aim: Evidence on how the pace of television and film editing affects children's behaviour and attention is inconclusive. We examined whether a fast‐paced film affected how preschool‐aged children interacted with toys. Methods: The study comprised 70 children (36 girls) aged two to four‐and‐a‐half years who attended preschools in Essex, United Kingdom. The children were paired up and tested with either a fast‐ or a slow‐paced film of a narrator reading a children's story. The fast‐paced version had 102 camera cuts and 16 still images, and the slow‐paced version had 22 camera cuts and four still images. Each dyad took part in two video‐recorded free‐play sessions, before and after they watched one of the specially edited four‐minute films. The number of toys the children played with before and after the film sessions was recorded. Results: Before they watched the films, the children's behaviour did not differ between the groups. However, after watching the film, the children in the fast‐paced group shifted their attention between toys more frequently than the children who watched the slow‐paced film. Conclusion: Even a brief exposure to differently paced films had an immediate effect on how the children interacted with their toys.